IMPLEMENTASI KONSEP PENTAHELIX DALAM PENGEMBANGAN DESA WISATA CIBUNTU - Pusparani; Rianto (Bogor Hospitality Journal, 2021)
Cibuntu Village is one of the villages in Kuningan Regency which has various tourist destinations and attractive natural beauty. The success of developing the tourism sector cannot be separated from the synergistic collaboration of various parties. The Ministry of Tourism, through Permen number 14/2016 on Guidelines for Sustainable Tourism Destinations, emphasizes that there is need for optimal interconnection between the business, government, community, academic and media (BGCAM) sectors in building the tourism sector or more commonly known as the Penta Helix Concept so that tourism can provide benefits to society. To see the extent to which the Penta Helix concept has been applied in the development of the Cibuntu tourist village, this research was conducted. This research is a case study, the sources in this research are five peoples who are representatives of business people, government, community, academics and the media. The results show that the implementation of the Penta helix concept has gone well. The synergic coordination and collaboration of each Penta helix element has led to Cibuntu Tourism Village winning several awards in the tourism sector. The coordination and collaboration that has been built between the government, tourism business actors, communities, academics, and the media need to be maintained.